Social and Economic Challenges to Implementing the Ketogenic Diet: A Case Series - Lynch, Sloan; Barry, Catherine; Douglass, Laurie M. (Journal of Pediatric Epilepsy, 2020)
The ketogenic diet (KD) is a powerful therapeutic tool that can reduce seizure activity in patients with refractory epilepsy. However, dietary implementation can be difficult for patients and families due to the time and resource intensive nature of the diet. These challenges are particularly pronounced in economically disadvantaged or socially unstable patient populations. The first case of this series describes the successful implementation of KD in a low-income, homeless patient through the use of innovative KD recipes and access to social programs offered through Boston Medical Center. The second case illustrates the importance of consistent parental support to the success of KD and describes mechanisms used to improve familial support within a nonunified household. Collectively, these cases demonstrate ways by which health care providers can make this powerful dietary treatment accessible to low-resource patients.
Keywords: ketogenic diet; epilepsy; socioeconomic barriers